2013
DOI: 10.1039/c3cs60085h
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule force spectroscopy of G-protein-coupled receptors

Abstract: The applicability of single-molecule force spectroscopy (SMFS) to characterize membrane proteins in vitro is developing rapidly and opening a wide range of fascinating possibilities to study how intra- and intermolecular interactions determine their structural stability and functional state. In particular, understanding how molecular interactions contribute to the functional state of G-protein-coupled receptors (GPCRs) is of importance because they mediate most of our physiological responses and act as therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 110 publications
4
28
0
Order By: Relevance
“…Because SMFS spectra recorded upon unfolding of PAR1 closely resembled those previously recorded for the human β 2 -adrenergic receptor (β 2 AR) 12 , a class A GPCR showing high structural homology to PAR1 (ref. 13), we concluded that PAR1 folded correctly into the proteoliposomes 14 . For FD-based AFM we imaged PAR1 proteoliposomes adsorbed onto freshly cleaved mica in buffer solution at 37 °C ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Because SMFS spectra recorded upon unfolding of PAR1 closely resembled those previously recorded for the human β 2 -adrenergic receptor (β 2 AR) 12 , a class A GPCR showing high structural homology to PAR1 (ref. 13), we concluded that PAR1 folded correctly into the proteoliposomes 14 . For FD-based AFM we imaged PAR1 proteoliposomes adsorbed onto freshly cleaved mica in buffer solution at 37 °C ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…AFM-based SMFS characterizes the mechanical and kinetic stability of the structural intermediates of GPCRs at the resolution of single α-helices [ 34 ] or a few amino acids [ 35 • ]. In a nutshell, the tip of the AFM cantilever acts as a ‘sticky finger’ to pick up single membrane receptors from either terminal end.…”
Section: Single-molecule Force Spectroscopy Of Gpcrs In Membranesmentioning
confidence: 99%
“…Differences in the extent with which unfolding intermediates are observed in aoTTR in comparison to nTTR are suggestive of considerable folding differences, and also of stabilization of unfolding intermediates of the aoTTR dimer by its neighboring environment. To illustrate this last point, we may take the example of 2 different classes of α‐helical proteins: while membrane‐embedded G‐protein coupled receptors tend to unfold via the stepwise unraveling of their individual transmembrane α‐helices, soluble α‐helical bundles of spectrin unfold in a single event . Likewise, mechanical unfolding of β‐barrel membrane proteins such as OmpG reveals multiple unfolding intermediates while the water‐soluble β‐barrel GFP does not .…”
Section: Discussionmentioning
confidence: 99%
“…The double-stack arrangement of aoTTR likely contributes to stabilize unfolding intermediates. D, Diagram of the assembly of annular oligomers with monomers oriented in a head-to-head and tail-to-tail configuration forming strong and weakly interacting interfaces of α-helical proteins: while membrane-embedded G-protein coupled receptors tend to unfold via the stepwise unraveling of their individual transmembrane α-helices, 49 soluble α-helical bundles of spectrin unfold in a single event. 50 Likewise, mechanical unfolding of β-barrel membrane proteins such as OmpG reveals multiple unfolding intermediates while the water-soluble β-barrel GFP does not.…”
Section: Contour Length Of Unfolding Intermediatesmentioning
confidence: 99%